Modelling quality teaching among teachers of the Islamic private secondary schools in Southern Thailand - Da-i, Naruemon (Kulliyyah of Education, International Islamic University Malaysia, 2016)
The primary purpose of this study was to investigate the relationship among three factors namely, Effective School Management (ESM), Teacher Efficacy (TE) and Quality Teaching (QT). A sample of 585 teachers from forty-seven Islamic private secondary schools in Songkhla Thailand participated in this study. This study utilized both Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) to establish the psychometric properties of each construct. The results of EFA and CFA demonstrated that ESM represented by five distinct factors, while TE by three distinct factors and QT by two distinct factors. In addition, the results from measurement models also found evidence of construct validity and reliability for the factors that constituted the three constructs (ESM, TE, and QT). The re-specified model was tested as the data did not fit the hypothesized model. Based on the new model, it was found that ESM and TE influenced QT. The model revealed that five-factor of ESM, namely Strong Instructional Leadership (SIL), Safe and Orderly Environment (SOE), Frequency Monitoring Student Progress (FMS), Opportunity to Learn and Time on Task (OtL), and School and Home Relationship (SHR) has directly influenced QT. Similarly, three-factor of TE namely, efficacy for Student Engagement (StdE), efficacy for Instructional Strategy (IS) and efficacy for Classroom Management (CMg) is directly influenced QT. However, for QT, it was explained by one-factor model. The study also conducted invariant analyses of gender and teaching experience. Both gender and teaching experience were found to have no moderating impact on full-fledged structural model of Quality-Teaching (Q-T). The findings suggested that quality teaching required concerted effort from various parties, particularly school management and teachers themselves. Furthermore, Islamic private secondary schools should organize programmes such as workshops on pedagogy and material development for teachers to educate them about the importance of the quality teaching.